Pelatihan Pendampingan Untuk Standarisasi Protokol Anestesi di RS UNS Surakarta - Tri Budi Santoso; Andang Sudarmono (Lembaga Pengembangan Kinerja Dosen, 2024)
Standardization of anesthesia protocols is essential to improve patient safety and work efficiency of medical personnel. This mentoring training aims to improve the understanding and skills of medical personnel in implementing anesthesia protocols that comply with international standards. This study used a quantitative method with a pre-experimental one-group pre-test and post-test design. Respondents consisted of 20 medical personnel working at UNS Surakarta Hospital. The results of the study showed a significant increase in the understanding and skills of medical personnel after being given training, as indicated by a significant difference in pre-test and post-test scores.